Fuzzy Chance-Constrained Day-Ahead Operation of Multi-Building Integrated Energy Systems: A Bi-Level Mixed Game Approach - Jingjing Zhai; Guanbin Shen; Chengao Li; Haoming Liu (Buildings, 2025)
This paper proposes a novel mixed game-based day-ahead operation strategy for multi-building integrated energy systems, which innovatively addresses both inter-building cooperation and non-cooperative energy transactions with system operators under uncertainties. Specifically, a bi-level operation model is established in which the upper level maximizes the benefits of the energy system operator, and the lower level minimizes the costs of multiple buildings. Then, in consideration of source-load uncertainties in multiple building energy systems, the fuzzy chance-constrained programming method is introduced, and the clear equivalent class method is used to reformulate the fuzzy chance constrained model into a tractable deterministic type. Further, a privacy-preserving hierarchical solution approach is presented to solve the bi-level optimization model, and the Shapley value method is adopted for benefits redistribution. Case studies on a multi-building system in East China showcase the effectiveness of the proposed work and demonstrate that the proposed strategy contributes to reducing the operation costs of the multi-building system by approximately 3.98% and increasing the revenue of the energy system operators by 10.31%.